Loss of Retinal Function and Pigment Epithelium Changes in a Patient with Common Variable Immunodeficiency - Jakob Halborg; Torben L. Sørensen (Case Reports in Ophthalmological Medicine)
Common variable immunodeficiency (CVID) has only scarcely been associated with ocular symptoms and rarely with retinal disease. In this case we describe a patient with distinct morphological and functional alterations in the retina. The patient presents with characteristic changes in retinal pigment epithelium, autofluorescence, and electrophysiology.